1998
DOI: 10.1121/1.423051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tensile loading on the properties of elastic-wave propagation in a strand

Abstract: Effects of tensile loading on the properties of longitudinal-mode elastic-wave propagation in a 1.52-cm-diam, seven-wire strand used for prestressed concrete structures were investigated experimentally. In an unloaded state, the wave propagation properties in strand matched those seen in individual wires comprising the strand, namely, straight center wire and helical outer wires. In the strand, however, extraneous signals were found to be produced from the propagating wave due to physical interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 6 publications
4
60
1
Order By: Relevance
“…In this method, the ultrasonic wave is sent into the material and based on the variations made in transfer velocity or resonance frequency due to the acoustoelastic effect, the existing stress field in the structure is estimated. This method has numerous application in estimating residual stress field in welded steel plates (Salamanca & Bray, 1996;Tanala, et al, 1995), railways (Hirao, et al, 1994;Szelażek, 1992), rods (Chen, et al, 1998) and multi-wire stands (Chen & Wissawapaisal, 2002;DiScalea, et al, 2003;Kwun & K. A. Bartels, 1998;Rizzo, et al, 2003;Washer, et al, 2002). Another area of usage for acoustoelastic-based methods is their application in detection of the looseness degree of bolts and assuring the adequacy of axial force on joints (Chaki, et al, 2006;Chaki, 2007;Johnson, et al, 1996).…”
Section: Acoustoelastic Effect Based Methodsmentioning
confidence: 99%
“…In this method, the ultrasonic wave is sent into the material and based on the variations made in transfer velocity or resonance frequency due to the acoustoelastic effect, the existing stress field in the structure is estimated. This method has numerous application in estimating residual stress field in welded steel plates (Salamanca & Bray, 1996;Tanala, et al, 1995), railways (Hirao, et al, 1994;Szelażek, 1992), rods (Chen, et al, 1998) and multi-wire stands (Chen & Wissawapaisal, 2002;DiScalea, et al, 2003;Kwun & K. A. Bartels, 1998;Rizzo, et al, 2003;Washer, et al, 2002). Another area of usage for acoustoelastic-based methods is their application in detection of the looseness degree of bolts and assuring the adequacy of axial force on joints (Chaki, et al, 2006;Chaki, 2007;Johnson, et al, 1996).…”
Section: Acoustoelastic Effect Based Methodsmentioning
confidence: 99%
“…The effect of acoustoelastic phenomenon on the time-of-flight increase was observed, however, its quantification in terms of acoustoelastic coefficient was not achieved. In the same year Kwun et al [13] exploited the dispersive behavior of ultrasonic guided waves to evaluate stress levels in seven-wire prestressed strands. It was shown that a portion of the frequency components, namely in high frequency range, would disappear from the guided wave frequency spectrum with increasing tensile stress.…”
Section: Introductionmentioning
confidence: 99%
“…Exploitation of the acoustoelastic effect concerns various industrial applications, such as residual stresses in welded steel plates [3,4] and railroad rails [5,6], tightening of bolts [7][8][9] and stress levels in bars [10] or in multi-wire strands [11][12][13][14][15]. All of studies concerning the acoustoelastic measurements in waveguides were carried out using ultrasonic guided waves, especially the fundamental mode L(0,1).…”
Section: Introductionmentioning
confidence: 99%
“…For cylindrical waveguides, three types of propagation modes may be identified: longitudinal (L), flexural (F) and torsional (T) models [6]. Assuming a solid cylinderical rod, longitudinal guided wave is axis symmetric, including radial and axial displacement components.…”
Section: Theoretical Analysismentioning
confidence: 99%